Antimicrobial Resistance and Attributable Burden of Pseudomonas aeruginosa in Hospitalized Patients. (4th October 2017) - Zhang, Dongmu; Hawkshead, John; Merchant, Sanjay
Abstract: Background: Pseudomonas aeruginosa ( PA ) is a leading cause of nosocomial infections. Multi-drug-resistant (MDR) PA is an increasing problem. The study objectives were to estimate PA prevalence in hospitalizations, rates of MDR PA and carbapenem-resistant (CR) PA, incremental hospital length of stay (LOS), and hospital cost attributable to MDR PA and CR PA . Methods: This retrospective cohort study identified hospitalizations for MDR and CR PA with available diagnosis, laboratory, and medication data from October 1, 2013 to September 30, 2015 using the Cerner Health Facts ® database. Hospitalizations with LOS <24 hours or >3x the SD of the cohort mean were excluded. MDR was defined as intermediate or resistant to at least one drug in 3 of 5 classes: aminoglycosides, extended spectrum cephalosporins, fluoroquinolones, carbapenems, and piperacillin or piperacillin-tazobactam. CR was defined as intermediate or resistant to meropenem or imipenem. Hospitalizations for MDR and non-MDR PA and for CR and non-CR PA were matched 1:1 by propensity score. Mean (SD) and median LOS (days) and total hospital cost (US $) were reported. Results: A total of 1, 045, 038 hospitalizations were identified. The average patient age was 50 (SD = 27) and 57.5% were female. PA prevalence was 10.8/1, 000 hospitalizations. Among hospitalizations for PA, the MDR rate was 12.3% and the CR rate was 14.5%. MDR and CR rates were higher in ICU (19.0% and 20.1%) than non-ICU hospitalizations (11.6% and 13.9%). Hospital LOS and total cost were significantly higher for the MDR PA group than the non-MDR PA group. Similarly higher LOS and total cost were observed in the CR group. Conclusion: Our findings highlight the high rates of PA, particularly in the ICU, and the substantial economic burden associated with MDR and CR PA . Decision-makers must evaluate optimal treatment strategies and antimicrobial stewardship measures to minimize the economic impact of these infections and improve clinical outcomes in hospitalized patients. Disclosures: D. Zhang, Merck: Employee, Salary. J. Hawkshead III, Merck: Employee, Salary. S. Merchant, 1Merck & Co., Inc.: Employee and Shareholder, Salary